Pengaruh Layanan Informasi Melalui Daring terhadap Peningkatan Minat Studi Lanjut ke Perguruan Tinggi pada Siswa SMAN 3 Sukoharjo - Mahmuddah Dewi Edmawati; Aldila Fitri Radite Nur Maynawati; Candra Giri Murti (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2021)
Abstract: This study aims to find out how the influence of online information services can increase the interest of SMA N 3 Sukoharjo students to continue their studies in higher education. The method in this study the researchers used quantitative experimental methods. Quantitative research does not question the relationship between researchers and research subjects because research results depend more on the instruments used and the measurable variables used, rather than on the intimate and emotional involvement between researchers and the subjects studied. The results of the study were that there was a significant effect on the provision of online information services to students of class XI MIPA 3 SMA Negeri 3 Sukoharjo in the 2020/2021 academic year to continue their education to higher education. The results of the study using the calculation of the Paired Sample T-Test in the Pre Test and Post Test showed a significance value (2-tailed) 0.000 <0.05, meaning that there was a significant difference between the initial variable and the final variable. This shows that there is a significant effect on the treatment given to each variable. So it can be concluded that: "There is an influence of providing online information services regarding further studies on the interest of class XI MIPA 3 students at SMA Negeri 3 Sukoharjo in the 2020/2021 academic year to continue their education to higher education. Keywords: information service, online, interest in further study